Pulmonary vascular adaptations to hypoxia in elite breath-hold divers - Kjeld, Thomas; Isbrand, Anders Brenøe; Arendrup, Henrik Christian; Højberg, Jens; Bejder, Jacob; Krag, Thomas O.; Vissing, John; Tolbod, Lars Poulsen; Harms, Johannes Hendrik; Gormsen, Lars Christian; Fuglø, Dan; Hansen, Egon Godthaab (Frontiers in Physiology, 2024)
Introduction Elite breath-hold divers (BHD) possess several oxygen conserving adaptations to endure long dives similar to diving mammals. During dives, Bottlenose Dolphins may increase the alveolar ventilation (VA) to perfusion (Q) ratio to increase alveolar oxygen delivery. We hypothesized that BHD possess similar adaptive mechanisms during apnea. Methods and results Pulmonary blood volume (PBV) was determined by echocardiography, 15O-H2O PET/CT, and cardiac MRi, (n = 6) during and after maximum apneas. Pulmonary function was determined by body box spirometry and compared to matched controls. After 2 min of apnea, the PBV determined by echocardiography and 15O-H2O-PET/CT decreased by 26% and 41%, respectively. After 4 min of apnea, the PBV assessed by echocardiography and cardiac MRi decreased by 48% and 67%, respectively (n = 6). Fractional saturation (F)O2Hb determined by arterial blood-gas-analyses collected after warm-up and a 5-minute pool-apnea (n = 9) decreased by 43%. Compared to matched controls (n = 8), spirometry revealed a higher total and alveolar-lung-capacity in BHD (n = 9), but a lower diffusion-constant. Conclusion Our results contrast with previous studies, that demonstrated similar lung gas transfer in BHD and matched controls. We conclude that elite BHD 1) have a lower diffusion constant than matched controls, and 2) gradually decrease PBV during apnea and in turn increase VA/Q to increase alveolar oxygen delivery during maximum apnea. We suggest that BHD possess pulmonary adaptations similar to diving mammals to tolerate decreasing tissue oxygenation. New and noteworthy This manuscript addresses novel knowledge on tolerance to hypoxia during diving, which is shared by elite breath-hold divers and adult diving mammals: Our study indicates that elite breath-hold divers gradually decrease pulmonary blood volume and in turn increase VA/Q, to increase alveolar oxygen delivery during maximum apnea to tolerate decreasing oxygen levels similar to the Bottlenose Dolphin.